2001
DOI: 10.1046/j.1532-5415.2001.4911234.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Metabolism in Japanese Centenarians: Effects of Apolipoprotein E Polymorphism and Nutritional Status

Abstract: Low levels of apo B-containing lipoproteins attributable to a genetic cause may be advantageous for longevity. Lipoprotein profiles in centenarians were consistently related to the subjects' nutritional status, inflammation markers, and apo E polymorphisms. The results provide evidence for the importance of maintaining nutritional status in the very old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…They did not find any significant difference in lipid or apolipoprotein levels, however, the HDL2b level was increased, and the HDL3a level decreased in centenarians, compared to those in the controls (9). We have also demonstrated relatively higher levels of HDL2-C among 42 centenarians by ultracentrifugation (11). Recently, nuclear magnetic resonance (NMR) spectroscopy was efficiently applied for the quantification of lipoprotein particle size (14,15).…”
Section: Hdl Cholesterol and Its Subpopulations In Centenariansmentioning
confidence: 70%
See 3 more Smart Citations
“…They did not find any significant difference in lipid or apolipoprotein levels, however, the HDL2b level was increased, and the HDL3a level decreased in centenarians, compared to those in the controls (9). We have also demonstrated relatively higher levels of HDL2-C among 42 centenarians by ultracentrifugation (11). Recently, nuclear magnetic resonance (NMR) spectroscopy was efficiently applied for the quantification of lipoprotein particle size (14,15).…”
Section: Hdl Cholesterol and Its Subpopulations In Centenariansmentioning
confidence: 70%
“…However, results from centenarian studies have been conflicting. Some investigators have reported that centenarians showed a lipid profile similar to that of the middle-aged population (9), but others have demonstrated lower total and HDL cholesterol in centenarians (10,11). This discrepancy may be attributable to differences in sampling, and the nutritional and functional status of centenarians (this issue is also described in later paragraphs).…”
Section: Hdl Cholesterol and Its Subpopulations In Centenariansmentioning
confidence: 91%
See 2 more Smart Citations
“…This conclusion apparently clashes with the results of several previous epidemiological surveys, concluding that elevated plasma lipoprotein(a) concentration is a rather frequent finding in centenarians. [2][3][4][5][6] This apparent paradox has engaged the minds of several scientists for many years, trying to find a reliable bridge between the cardiovascular potency of elevated concentrations of this elusive lipoprotein and human longevity. [7][8] Apolipoprotein(a), which characterizes lipoprotein(a), is constituted by an inactive protease domain, a single copy of the plasminogen kringle V and multiple repeats of domains homologous to the plasminogen kringle IV.…”
mentioning
confidence: 99%